Peningkatan Pengetahuan Buruh Tani Akan Bahaya Pestisida dan Penggunaan Alat Pelindung Diri Yang Benar Melalui Penyuluhan - Supangat Supangat; Jauhar Firdaus; Elly Nurus Sakinah; Laksmi Inreswari; Aris Prasetyo (Journal of Community Development, 2023)
Farm labor is one of the main livelihoods in Indonesia. Farmers' activities on agricultural land are never separated from the use of pesticides, although basically pesticides are not only harmful to plant pests but also pose a potential hazard to farm workers as pesticide users. Various types of pesticides circulating and used in Indonesia include the type of organophosphate. Jam because of its affordable price, organophosphates have good effectiveness in controlling plant pests. This ability is comparable to the dangers of organophosphates for health. Various studies have proven that organophosphate pesticides and other pesticides can cause both acute and chronic health problems. Health problems can range from mild to severe symptoms resulting in disability or death. Pesticides intoxication can actually be prevented. One of the prevention efforts that can be done is the use of good and correct Personal Protective Equipment (PPE). Farmers actually know about the potential dangers of pesticides and the importance of using PPE when spraying pesticides. However, most farm workers do not use standard PPE and do not know how to use the correct PPE. They choose to use simple PPE that they make themselves, for example using t-shirts as head coverings and face masks instead of using hats, goggles and masks as face and head protection. These measures are, of course, non-standard and cannot provide perfect protection. The community service that is carried out has the target of farm workers who live in Gayasan Village, Jenggawah District, Jember Regency. This community service activity uses counseling methods and training on the proper and correct use of PPE, accompanied by the implementation of free health checks and medication for farm laborers and the surrounding community. Measurement of the level of knowledge is measured using a questionnaire and then compared between before and after counseling. The results obtained are an increase in the knowledge of farm workers about the dangers of pesticides and the use of good and standard PPE.